Low cost wastewater bioremediation technology innovative treatment of sulphate and metal-rich wastewater - Bhattacharyaa, Jayanta; Dev, Subhabrata; Das, Bidus (Butterworth-Heinemann, 2018)
Low Cost Wastewater Bioremediation Technology: Innovative Treatment of Sulphate and Metal Rich Wastewater provides users with an authoritative guide on the technologies, processes and considerations needed for the treatment of Sulphate and Metal rich wastewaters. In this book, the authors not only explain the associated technologies, but also provide suitable alternatives to commercial treatment in terms of performance and cost effectiveness. As enormous quantities of sulphates and metal-rich contaminates are released into the environment each year, the technologies noted in the book provide the most eco-friendly, low cost and efficient alternatives available.--Provided by publisher.